35. INTERNATIONAL COLLABORATIVE EFFORTS IN THE ENIGMA SCHIZOPHRENIA WORKING GROUP - Turner, Jessica (Schizophr Bull, 2019)
Psychiatric disorders are notoriously heterogeneous in their clinical presentation and course. Neuroimaging analyses also have been plagued with false positive findings from small sample sizes. The relationship between clinical measures and brain structure or function is distorted by medication and other environmental effects. The ENIGMA consortium (Enhancing Neuroimaging Genetics through Meta Analyses) was started in 2010 to address similar problems in imaging genetics—small and unreliable relationships which are distorted by environmental effects, requiring extremely large sample sizes. From a focus on genome-wide effects on brain structure, it has expanded to include over 50 working groups and over 100 projects ongoing, with representation from 39 countries. I will focus on the ENIGMA Schizophrenia working group and related projects. Through planned meta-analyses of legacy datasets, we have definitively addressed the distribution of differences in brain volumes both cortically and subcortically in schizophrenia; and similar approaches have been applied to white matter tracts. This has fostered newer analyses of different brain measures, such as subcortical shape, and closer examinations of symptom severity relationships. Newer groups have been formed to address issues not covered by ENIGMA SZ or other disease-focused groups, to examine the brain relationships in families, in early onset psychosis, in clinical high-risk groups, or schizotypy studies. With some groups in existence since 2012 and new groups being formed every year, the opportunities for cross-disorder analyses are numerous, and the working group focusing on 22q deletions has already demonstrated that value. I will present the highlights of the ENIGMA SZ work both within SZ and across disorders, as well as discussing the new directions of infrastructure to address the challenges of international imaging collaborations.